2012
DOI: 10.1111/jocd.12013
|View full text |Cite
|
Sign up to set email alerts
|

The tolerability profile of clindamycin 1%/benzoyl peroxide 5% gel vs. adapalene 0.1%/benzoyl peroxide 2.5% gel for facial acne: results of a randomized, single‐blind, split‐face study

Abstract: Clindamycin/BPO had a better tolerability profile than adapalene/BPO during 2 weeks of split-face treatment. Treatment satisfaction was highest with clindamycin/BPO.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 7 publications
0
21
0
2
Order By: Relevance
“…1,2, Three studies prohibited the use of moisturizers, while other studies provided or allowed moisturizer use. 5,7,10 In all studies, tolerability (including erythema, dryness, scaling, and burning) had been reported using different scales ranging from none to severe for each category. For each study, results had been analyzed to determine whether there was statistically significant difference in tolerability to the retinoids.…”
Section: Resultsmentioning
confidence: 99%
“…1,2, Three studies prohibited the use of moisturizers, while other studies provided or allowed moisturizer use. 5,7,10 In all studies, tolerability (including erythema, dryness, scaling, and burning) had been reported using different scales ranging from none to severe for each category. For each study, results had been analyzed to determine whether there was statistically significant difference in tolerability to the retinoids.…”
Section: Resultsmentioning
confidence: 99%
“…A post hoc analysis, which was conducted to determine on which side of the face AEs occurred, indicated that treatment related AEs, including irritation, dryness, and erythema, were significantly less common with C/BPO than the adapalene 0.1%/benzoyl peroxide 2.5% gel (A/BPO) (P≤0.01)." 67 Example 3-"Minor and transient adverse reactions included herpes simplex virus reactivation (confined to the lips) (one patient, 3.5%)." 68 Explanation-Presentation of harms or unintended effects at the body site (examples 1 and 2) and at the participant level (example 3) is important for within person randomised trials.…”
Section: Item 19: Harmsmentioning
confidence: 99%
“…There were no serious AEs. A post hoc analysis, which was conducted to determine on which side of the face AEs occurred, indicated that treatment related AEs, including irritation, dryness, and erythema, were significantly less common with C/BPO than the adapalene 0.1%/benzoyl peroxide 2.5% gel (A/BPO) (P≤0.01).”…”
Section: Resultsmentioning
confidence: 99%